Early discharge hospital at home - Gonçalves-Bradley, D; Iliffe, S; Doll, H; Shepperd, S (John Wiley & Sons, Ltd., 2017)
Background Early discharge hospital at home is a service that provides active treatment by healthcare professionals in the patient's home for a condition that otherwise would require acute hospital inpatient care. This is an update of a Cochrane review. Objectives To determine the effectiveness and cost of managing patients with early discharge hospital at home compared with inpatient hospital care. Search methods We searched the following databases to 9 January 2017: the Cochrane Effective Practice and Organisation of Care Group (EPOC) register, Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, CINAHL, and EconLit. We searched clinical trials registries. Selection criteria Randomised trials comparing early discharge hospital at home with acute hospital inpatient care for adults. We excluded obstetric, paediatric and mental health hospital at home schemes. Data collection and analysis We followed the standard methodological procedures expected by Cochrane and EPOC. We used the GRADE approach to assess the certainty of the body of evidence for the most important outcomes. Main results We included 32 trials (N = 4746), six of them new for this update, mainly conducted in high-income countries. We judged most of the studies to have a low or unclear risk of bias. The intervention was delivered by hospital outreach services (17 trials), community-based services (11 trials), and was co-ordinated by a hospital-based stroke team or physician in conjunction with community-based services in four trials. Studies recruiting people recovering from stroke Early discharge hospital at home probably makes little or no difference to mortality at three to six months (risk ratio (RR) 0.92, 95% confidence interval (CI) 0.57 to 1.48, N = 1114, 11 trials, moderate-certainty evidence) and may make little or no difference to the risk of hospital readmission (RR 1.09, 95% CI 0.71 to 1.66, N = 345, 5 trials, low-certainty evidence). Hospital at home may lower the risk of living in institutional setting at six months (RR 0.63, 96% CI 0.40 to 0.98; N = 574, 4 trials, low-certainty evidence) and might slightly improve patient satisfaction (N = 795, low-certainty evidence). Hospital at home probably reduces hospital length of stay, as moderate-certainty evidence found that people assigned to hospital at home are discharged from the intervention about seven days earlier than people receiving inpatient care (95% CI 10.19 to 3.17 days earlier, N = 528, 4 trials). It is uncertain whether hospital at home has an effect on cost (very low-certainty evidence). Studies recruiting people with a mix of medical conditions Early discharge hospital at home probably makes little or no difference to mortality (RR 1.07, 95% CI 0.76 to 1.49; N = 1247, 8 trials, moderate-certainty evidence). In people with chronic obstructive pulmonary disease (COPD) there was insufficient information to determine the effect of these two approaches on mortality (RR 0.53, 95% CI 0.25 to 1.12, N = 496, 5 trials, low-certainty evidence). The intervention probably increases the risk of hospital readmission in a mix of medical conditions, although the results are also compatible with no difference and a relatively large increase in the risk of readmission (RR 1.25, 95% CI 0.98 to 1.58, N = 1276, 9 trials, moderate-certainty evidence). Early discharge hospital at home may decrease the risk of readmission for people with COPD (RR 0.86, 95% CI 0.66 to 1.13, N = 496, 5 trials low-certainty evidence). Hospital at home may lower the risk of living in an institutional setting (RR 0.69, 0.48 to 0.99; N = 484, 3 trials, low-certainty evidence). The intervention might slightly improve patient satisfaction (N = 900, low-certainty evidence). The effect of early discharge hospital at home on hospital length of stay for older patients with a mix of conditions ranged from a reduction of 20 days to a reduction of less than half a day (moderate-certainty evidence, N = 767). It is uncertain whether hospital at home has an effect on cost (very low-certainty evidence). Studies recruiting people undergoing elective surgery Three studies did not report higher rates of mortality with hospital at home compared with inpatient care (data not pooled, N = 856, low-certainty evidence; mainly orthopaedic surgery). Hospital at home may lead to little or no difference in readmission to hospital for people who were mainly recovering from orthopaedic surgery (N = 1229, low-certainty evidence). We could not establish the effects of hospital at home on the risk of living in institutional care, due to a lack of data. The intervention might slightly improve patient satisfaction (N = 1229, low-certainty evidence). People recovering from orthopaedic surgery allocated to early discharge hospital at home were discharged from the intervention on average four days earlier than people allocated to usual inpatient care (4.44 days earlier, 95% CI 6.37 to 2.51 days earlier, , N = 411, 4 trials, moderate-certainty evidence). It is uncertain whether hospital at home has an effect on cost (very low-certainty evidence). Authors' conclusions Despite increasing interest in the potential of early discharge hospital at home services as a less expensive alternative to inpatient care, this review provides insufficient evidence of economic benefit (through a reduction in hospital length of stay) or improved health outcomes.